Effect of Structured Diabetic Foot Exercise on Ankle–Brachial Index and Foot Sensitivity in Patients with Type 2 Diabetes Mellitus - Lestari, Intan Desi Tri; Sari, Nova Nurwinda; Sulastri, Diah (Inspirasi Foundation, 2026)
Objective: Type II Diabetes Mellitus is a chronic disease with an increasing incidence each year and can lead to complications such as neuropathy and peripheral circulatory disorders in the lower extremities. Structured diabetic foot exercise is a non-pharmacological intervention that has the potential to improve foot perfusion and sensitivity. This study aimed to determine the effect of structured diabetic foot exercise on the Ankle Brachial Index (ABI) values and foot sensitivity in patients with Type II Diabetes Mellitus at Kedaton Public Health Center. Method: This research employed a quantitative method with a pre-experimental design using a one-group pretest–posttest approach. The study population consisted of patients with Type II Diabetes Mellitus without diabetic ulcers. A total of 30 respondents were selected using purposive sampling. Data analysis included descriptive analysis and the Wilcoxon Signed Rank Test with a significance level of 95% (p-value < 0.05). Result The results showed that before the intervention, 14 respondents (46.7%) had normal ABI values (>1.0) and 14 respondents (46.7%) were in the borderline category (0.6–0.8). Most respondents (66.7%) had neuropathy (>3 points) in the pretest foot sensitivity assessment. After the intervention, 27 respondents (90.0%) had normal ABI values (>1.0), and 21 respondents (70.0%) were categorized as non-neuropathy (>7 points) in the posttest assessment. The Wilcoxon Signed Rank Test revealed p-values of <0.002 and <0.000. It can be concluded that structured diabetic foot exercise significantly affects ABI values and foot sensitivity in patients with Type II Diabetes Mellitus at Kedaton Public Health Center in 2025. Conclusion: Structured diabetic foot exercise can be recommended as an alternative intervention to improve ABI values and foot sensitivity in diabetic patients.